Mathematical Problem Solving Ability Viewed from Self-Efficacy of 7th Grade Students - Fatmasari, Hanindya Ranengtyas; Waluya, S.B; Sugianto, Sugianto (Unnes Journal of Mathematics Education Research, 2021)
Problem-solving ability is one of the standard mathematical abilities that students must have. This ability can be mastered well by students if students have affective abilities, one of which is self-efficacy. The aim of this research is to describe mathematical problem-solving abilities based on the self-efficacy of VII grade students in MTs Negeri 1 Semarang. This research method is descriptive qualitative. The technique of taking the subject was taken by six subjects by purposive sampling. The results showed that the description of mathematical problem solving abilities in terms of student self-efficacy varied, namely (1) students with high self-efficacy obtained six high category students' mathematical problem solving abilities and one medium category student and able to master four indicators of mathematical problem solving abilities is very well, (2) students with medium self-efficacy obtained mathematical problem solving abilities as much as one high category student, 18 medium category students, one low category student, but only good problem solving abilities on two indicators, (3) students with low self-efficacy, the results were five students in the medium category and two students in the low category, but they did not fully have complete mathematical problem solving abilities in all indicators of mathematical problem solving abilities.